2019
DOI: 10.4103/ijp.ijp_166_19
|View full text |Cite
|
Sign up to set email alerts
|

Case report on premature hair graying treated with Melitane 5% and oral hair supplements

Abstract: With chronological aging, hair turns gray. Untimely premature hair graying (PHG) may tremendously influence on cosmesis, self-credibility, and social life of the affected individuals. Consequently, early treatment is required to improve cosmetic appearance. To the best of our knowledge, until today, only one case of PHG is reported in the literature, and it occurred due to iron deficiency and successfully treated with ferrous sulfate. Herein, we delineate a case of PHG in a 14-year-old female treated with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…In patients with premature canities, that there was stimulation of melanocyte melanosome biogenesis and eumelanin synthesis in plucked hairs within 3 months 16 . Another α‐melanocyte‐stimulating hormone (α‐MSH) agonist, Melitane is also reported to reverse the premature graying of hair, 79 however, data regarding efficacy is very limited.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with premature canities, that there was stimulation of melanocyte melanosome biogenesis and eumelanin synthesis in plucked hairs within 3 months 16 . Another α‐melanocyte‐stimulating hormone (α‐MSH) agonist, Melitane is also reported to reverse the premature graying of hair, 79 however, data regarding efficacy is very limited.…”
Section: Resultsmentioning
confidence: 99%
“…23 In cases of vitiligo, the melanocytes are more sensitive to oxidative damage 78 and are more prone to premature graying. 16 Another α-melanocyte-stimulating hormone (α-MSH) agonist, Melitane is also reported to reverse the premature graying of hair, 79 however, data regarding efficacy is very limited.…”
Section: Other Co-morbid Conditions and Occurrence Of Pghmentioning
confidence: 99%
“…We envision this self-assembling strategy would lead to a successful drug like lanreotide. Since skin pigmentation disorders are associated with several diseases, including EPP, premature hair graying, and melanoma, this selective, potent MC1R agonist hydrogel is a promising, alternative approach for the treatment or prevention of these diseases. , …”
Section: Discussionmentioning
confidence: 99%
“…[27] Sakhiya et al reported repigmentation of gray hair following the use of 5 % melitane. [28] Melitane is a biomimetic peptide, agonist of alpha-MSH. It acts through binding melanocortin 1 receptor and thus stimulating the process of melanogenesis in hair.…”
Section: Investigationsmentioning
confidence: 99%